PERANCANGAN UI/UX VIXVEHICLE BERBASIS MOBILE MENGGUNAKAN PENDEKATAN WIREFRAME DENGAN METODE LEAN UX - Leonard, Rivaldo Louis; Hasniati; Bahri, Syamsul (KHARISMA Tech, 2026)
This study aims to design the user interface (UI) and user experience (UX) of VixVehicle, an online workshop service platform, using a wireframe approach and the Lean UX methodology. In the digital era dominated by mobile devices, VixVehicle faces significant challenges related to an unresponsive design and poor user experience, hindering accessibility and user convenience. To evaluate usability levels, this study employs the System Usability Scale (SUS), with initial scores indicating unsatisfactory results. The design process consists of several stages, including quantitative data collection through surveys, the identification of assumptions regarding user needs, the development of a Minimum Viable Product (MVP) prototype, and iterative testing to gather user feedback. The implementation of the new design led to an increase in the SUS score to 74.5, indicating a significant improvement in user experience. This enhancement demonstrates that the new design is more intuitive, responsive, and capable of increasing user engagement. The findings of this study are expected to serve as a reference for the development of similar applications, particularly in applying Lean UX principles to improve user satisfaction and ease of use in mobile-based applications.